2004
DOI: 10.1007/s10720-005-0011-2
|View full text |Cite
|
Sign up to set email alerts
|

Nanostructures with coherent boundaries and the local approach

Abstract: In our recent works [1,2], we analyzed the structural diversity of nanoparticles and the fragmentariness of their structure and formulated the statement that the structural inhomogeneity is a fundamental property of the nanostate. This statement was experimentally confirmed for a number of materials.In particular, reasoning from the results of neutron diffraction and X-ray diffraction investigations of ZrO 2 nanoparticles, Burkhanov et al. [3] proposed a twophase model allowing for the difference between the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
32
0

Year Published

2005
2005
2007
2007

Publication Types

Select...
7

Relationship

6
1

Authors

Journals

citations
Cited by 16 publications
(32 citation statements)
references
References 28 publications
(60 reference statements)
0
32
0
Order By: Relevance
“…These structures can exist only in the nanoworld. Let us demonstrate how an icosahedral diamond-like nanoparticle (icosahedral diamond) can be constructed if it is treated as a nanostructure that has coherent boundaries and is composed of (insignificantly distorted) fragments of diamond and lonsdaleite (hexagonal diamond).In our earlier works [12][13][14], we developed the local approach. Within this approach, nanoparticles with coherent boundaries in the general case are assembled from a limited set of building blocks (geometrical structural complexes) determined by the fundamental (specifically, projective) manifolds and the principles of assembling are governed by the topological properties of a fiber space.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…These structures can exist only in the nanoworld. Let us demonstrate how an icosahedral diamond-like nanoparticle (icosahedral diamond) can be constructed if it is treated as a nanostructure that has coherent boundaries and is composed of (insignificantly distorted) fragments of diamond and lonsdaleite (hexagonal diamond).In our earlier works [12][13][14], we developed the local approach. Within this approach, nanoparticles with coherent boundaries in the general case are assembled from a limited set of building blocks (geometrical structural complexes) determined by the fundamental (specifically, projective) manifolds and the principles of assembling are governed by the topological properties of a fiber space.…”
mentioning
confidence: 99%
“…Within this approach, nanoparticles with coherent boundaries in the general case are assembled from a limited set of building blocks (geometrical structural complexes) determined by the fundamental (specifically, projective) manifolds and the principles of assembling are governed by the topological properties of a fiber space. The geometrical structural complexes of tetrahedrally coordinated structures were derived and it was shown that fragments of crystalline and quasicrystalline structures can be joined together into a unified nanostructure with coherent boundaries [12]. In [15], it was demonstrated that the local approach allows one to explain different types of icosahedral packings [16,17] when they are considered mappings (onto the three-dimensional Euclidean space) of specific substructures of high-symmetry ndimensional structures ( n ≥ 3) of a fiber space specified by the Hopf bundle for the eight-dimensional root lattice E 8 .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The joining of the geometrical structural complex to an elementary-similar cluster (embedded in the same algebraic construction) provides a way of assembling nanostructures with coherent boundaries. 17,18 …”
Section: Resultsmentioning
confidence: 99%
“…For the given algebra and the root lattice E 8 the ring of invariants have a basis of homogeneous polytopes of degrees 2, 8,12,14,18,20,24,30, and the orbit of its isomorphism group is its spherical seven-scheme. Therefore, it is appropriate to consider v-schemes for v = 4, 6, 8, 12, 14 and the values of μ for known polytopes, which, in their turn, correspond to coordination spheres of the E 8 lattice and its sublattices.…”
Section: Structural Realization Of T-schemementioning
confidence: 99%